The Role of the Arabic Teacher in the Spread of Islam in Nusantara - Nur Ali (Yayasan Ilomata, 2021)
The entry of the people of the archipelago into Islam is the ability of Islamic broadcasters to use attractive packaging, especially by emphasizing conformity with Islam or continuity with local beliefs. This continuity does not mean changes in local religious beliefs or practices but adjustments through teaching. There are many methods used by Islamic broadcasters to get the people of the archipelago to accept Islamic teachings, such as a recitation teacher who teaches Arabic either directly or indirectly. Because the Al-Qur'an, the Prophet's Hadith and Islamic teachings use Arabic, the teachers try to teach Arabic well and professionally. Arabic was first taught with the aim that Islamic teachings could be understood and practiced properly. By practicing Islamic teachings properly and correctly, it becomes an attraction for people who have not embraced Islam. After the teachings of Islam have been well and correctly accepted, the aim of teaching Arabic has changed, namely to communicate with other nations.